DIVERSIDADE FÚNGICA EM SEMENTES DE FEIJÃO-FAVA - Mota, J. M.; Melo, M. P.; Silva, F. F. S.; Sousa, E. M. J.; Sousa, E. S.; Barguil, B. M.; Beserra Jr, J. E. A. (Revista Brasileira de Engenharia de Biossistemas, 2017)
There is no comprehensive survey of the presence of fungi associated with lima bean seeds. The objective of this study was to evaluate the fungal diversity of 34 samples of lima bean seeds, acquired with farmers and markets during the years 2014 and 2015 in the states of Ceará, Maranhão, Paraíba and Piauí. Subsamples of 400 seeds were sterilized by soaking in 1% NaOCl solution for 3 minutes, followed by two washes in sterile distilled water, and dried at room temperature. Seeds were placed in Petri plates containing Potato Dextrose Agar, and incubated at 25 °C for seven days. Fungal identification was based on morphological markers, and its incidences were quantified. Isolates from the main phytopathogens were also identified by the amplification and sequencing of housekeeping genes. Samples presented variations in diversity and incidence, with the presence of 22 fungal genera. Aspergillus spp., Penicillium spp., Curvularia sp. and Monilinia sp. corresponded to 63.76% of the colonies observed. Among the phytopathogens, isolates of Macrophomina phaseolina, Colletotrichum truncatum, Rhizoctonia solani, Fusarium udum and Fusarium oxysporum were identified by BLASTn analysis (99 to 100% DNA similarity) and phylogenetic analysis. C. truncatum and M. phaseolinapresented the highest incidences (0.95% and 1.58%, respectively) among phytopathogens.